Analisis Kimia Minyak Goreng Bekas Pedagang Gorengan Dengan Metode Deep Frying di Lingkungan Perguruan Tinggi Swasta Kota Jambi: Chemical Analysis of Cooking Oil Used by Street Vendors With Deep Frying Method in The Environment Of Private Universities in Jambi City - Wenny Octavia; Satiti Kawuri Putri; Arnati Wulansari (Media Publikasi Cendekia Indonesia, 2023)
Background: The largest demand for cooking oil in Indonesia is dominated by the use of coconut cooking oil with a breakdown of 8.954 million tons for palm cooking oil. Indonesia's most favorite food product is fried food. Fried food is one of the snacks that is always present when gathering. Examples of molen, fried tofu, fried tempeh, fried banana, fried bakwan, with deep frying methods that use a lot of oil, so that it has an impact on the use of cooking oil repeatedly and causes damage to cooking oil. Aims: aims to determine the chemical damage of used cooking oil based on the test parameters of water content, free fatty acid content and peroxide number content in accordance with the 2019 SNI palm cooking oil standard Methods: Descriptive non-experimental research is survey in nature, by collecting data interviews and questionnaires. This research was conducted in May-June 2023. The method of determining the sample is total sampling and univariate data processing. Results: The results showed that of the 10 samples of cooking oil used by fried food traders in private universities in Jambi City, there were 10% moisture content, 10% free fatty acid content and there were 100% peroxide number levels that did not meet the 2019 SNI standards. Conclusion: Of the 10 samples of used cooking oil from fried food traders in private universities in Jambi City, there was 1 sample of used cooking oil H that did not meet the 2019 SNI palm cooking oil quality standards